The Internationalization of Education Inspectorate through the Erasmus+ Programme - Martinez Pomet, Lola (Avances en Supervisión Educativa, 2025)
The Erasmus+ programme serves as a crucial strategy for the internationalisation of inspectorates of Education in Spain, fostering the modernisation of inspection services and enhancing educational quality from a European perspective. However, the General Action Plans across Spain's Autonomous Communities promote participation in Erasmus+ unevenly, resulting in limited involvement in Erasmus+ projects. Despite this, Educational Inspection Services have engaged in various Key Actions through multiple structures, enabling collaboration with European inspectors on a range of topics. This study examines how different administrations encourage participation in Erasmus+ for Inspection Services, reviews experiences within the European context, and evaluates proposals for the dissemination and exchange of results obtained from these projects.
Keywords: Erasmus; inspectorates; internationalization; European cooperation; dissemination; result exchange